Training Needs of Secondary School Mathematics Teachers in the Yemen Republic - Ahmed Dawod, Abdulhameed (2005)
There is a need to conduct a research on identifying the training needs, which is considered one of the most essential components of a staff development programme. The present status of planning in-service training programmes and workshops for Mathematics teachers in Yemen lacks appropriate methodology and a systematic and comprehensive assessment of the trainees' needs. In addition, no attention has been paid to systematically identify in-service needs for Mathematics teachers of secondary schools in Yemen. The purpose of this study was to identify the training needs of secondary schools Mathematics teachers in two urban cities Sana'a and Amran. The study focused on training needs as perceived by secondary school Mathematics teachers, supervisors and school administrators and identified the teachers' current practices of Mathematics teaching in secondary schools.The sample of the study was a sample six hundred and twelve consisting of 389 Mathematics teachers, 34 supervisors and 189 school administrators using a stratified random sampling technique. To obtain the data two instruments were used: (i) the new questionnaire was designed by the researcher. The questionnaire classified in-service training needs (59 items) into five categories which include: implementing of Mathematics instruction, planning of Mathematics instruction, evaluation of students in Mathematics instruction, diagnosing students7 needs in Mathematics instruction and classroom management. (ii) The observation instrument was modified and developed by Shian Leou (1998) which consisted of 35 items covering four domains, teaching skills, material organization and presentation, management of the learning environment and teaching attitudes. The observation was conducted among 30 secondary school Mathematics teachers in the classes and a video camera was used to record the lessons. Data were analyzed using the SPSS computer programme. The means, standard deviations, frequency and percentages were computed for the criteria indicators and independent one-way ANOVA and t-test were computed to determine significant differences between the means of the groups. The findings of the study revqaled that all the training needs represented necessary needs for Mathematics teachers in secondary schools and the teacher's current practice of Mathematics teaching was generally weak. These findings indicated highest needs in implementing of Mathematics instruction, followed by planning of Mathematics instruction, evaluation of students in Mathematics instruction, diagnosing students' needs in Mathematics instruction and classroom management. The One-way ANOVA revealed that there are no significant differences in perceptions of training needs between teachers, supervisors and school administrators in all domains. As for the variable of experience, a significant difference was found in the domains of classroom management and evaluation of students in Mathematics instruction. The effect of the t-test showed that there is no significant difference between male and female teachers in all domains. However, a significant difference was found between a variable of with educational and without educational background in the domain of evaluation of students in Mathematics instruction. The results of this study were consistent with previous findings in other specialization studies; therefore, it is recommended that a future study should do a comparative study on the training needs among Mathematics teachers in secondary schools and primary schools. A future replication of this study with comparison with other countries is necessary.